Pengembangan Model Pembelajaran Interaktif untuk Meningkatkan Motivasi dalam Belajar Bahasa Arab - Bangsa, Wira Nama Wira (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This study aims to develop an interactive learning model that can enhance students' motivation in learning Arabic. By utilizing a technology-based approach and active learning methods, it is expected that students will be more engaged in the learning process and achieve better results. The research was conducted in several high schools in Indonesia, focusing on measuring students' motivation and learning outcomes before and after the implementation of the interactive learning model. The results of the study show a significant increase in students' motivation and learning outcomes after the implementation of this model.